Intestinal protozoan infections among children 0-168 months with diarrhea in Mozambique: June 2014 - January 2018. - Adilson Fernando Loforte Bauhofer; Idalécia Cossa-Moiane; Selma Marques; Esperança L Guimarães; Benilde Munlela; Elda Anapakala; Jorfélia J Chilaúle; Marta Cassocera; Jerónimo S Langa; Assucênio Chissaque; Júlia Sambo; Lena Manhique-Coutinho; et al. (Public Library of Science (PLoS), 2020)
Background Intestinal parasites such as Cryptosporidium spp., Giardia lamblia and Entamoeba histolytica can cause severe diarrhea, especially among children in developing countries. This study aims to determine the frequency of Cryptosporidium spp., Giardia lamblia and Entamoeba histolytica in children with diarrhea and identify risk factors for infection. Methodology We conducted a cross-sectional study in children aged 0-168 months hospitalized with diarrhea in three regions of Mozambique, from June 2014 to January 2018. Following consent, caretakers were interviewed and a single stool specimen was collected from each child to diagnose Cryptosporidium spp., G. lamblia and E. histolytica using commercial immune-enzymatic assay (TechLab, Inc, Blacksburg, VA, USA). Anthropometric data were collected from the clinical reports. Multivariable logistic regression models were built to identify risk factors for Cryptosporidium spp. and G. lamblia infection. Results Twenty-one percent of all specimens (212/1008) presented at least one parasitic infection. Cryptosporidium spp. infection was the most common 12.0% (118/985), followed by G. lamblia 9.7% (95/983) and E. histolytica 2.0% (20/1004). Risk factors for infection by Cryptosporidium spp. were: provenience (children from Nampula province showed the highest risk, OR: 8.176; CI: 1.916-34.894; p-value < 0.01); animal contact (children with animal contact had a protective effect OR: 0.627; CI: 0.398-0.986; p-value < 0.05); underweight (children severely underweight showed a risk of 2.309; CI: 1.310-4.069; p-value < 0.05). Risk factors for infection by G. lamblia were: age (group with highest risk, 60-168 months (OR: 2.322; CI: 1.000-5.393, p-value > 0.05)); and living in a household with five or more members (OR: 2.141; CI: 1.286-3.565, p-value < 0.01). Conclusions Parasitic infection is common among children with diarrhea. Routine testing, standard treatment, and assessment for risk exposure of children with diarrhea should be implemented at health facilities in Mozambique.